New Hermite-Hadamard Type Inequalities for n-Times Differentiable and s-Logarithmically Preinvex Functions - Shuhong Wang; Ximin Liu (Abstract and Applied Analysis)
The concept of s-logarithmically preinvex function is introduced, and by creating an integral identity involving an n-times differentiable function, some new Hermite-Hadamard type inequalities for s-logarithmically preinvex functions are established.